(untitled) (Homiletic)
From the beginning of Latin American history, the pulpit has been the first line of defense of human dignity. This paper presents Oscar Romero as a distinguished witness to this tradition. His preaching life and death offer a short primer on the liberating message of the gospel. Romero’s Augustinian Christology coupled with the radio broadcasting of his sermons in the face of state resistance led him to express the preaching task in terms of the metaphor of a microphone. Christ is the best microphone of God; the church is the best microphone of Christ. For Romero, preaching Christ requires reading the Scriptures, the life of the church, and the signs of the times. When this happens the voice coming from the microphone sounds like many voices, like the voice of the voiceless, like the voice crying in the wilderness, and like the voice of the shepherd.